Ranking and Evaluation of Tight Sandstone Reservoirs and the Determination of the Lower Limit of Reservoir Physical Properties: A Case Study of Longfengshan Area in the Southern Songliao Basin, China. (25th May 2022) - Wang, Weiming; Liu, Yingnan; Miao, Changsheng; Liu, Yuhu; Qu, Xiyu; Zhang, Yangchen; La, Weihao; Lv, Qixia
Abstract : Ranking, evaluation, and the determination of the lower limit of physical properties (PPLL) are critical for selecting the sweet spots of tight reservoirs. This study investigated the tight reservoirs in the Longfengshan area in the southern Songliao Basin. Based on reservoir evaluation, this study determined the ranking criteria and the PPLL of tight sandstone reservoirs. The results are as follows. (1) Tight sandstone reservoirs can be divided into I, II, and III types based on the energy storage parameter and pore structure. Reservoirs with a porosity of > 6% are I-type reservoirs. The reservoirs of this type have high accumulation and seepage capacities, and their pore structures feature low displacement pressure and high structure coefficients. Reservoirs with a porosity of < 4% are III-type reservoirs. The reservoirs of this type have low accumulation and seepage capacities, and their pore structures feature high displacement pressure and low structure coefficients. The remaining reservoirs are II-type reservoirs. (2) The PPLL (denoted by porosity) of tight sandstone reservoirs was determined to be 2.50% using the water film thickness method and the minimum pore throat radius method. The water film thickness method, which comprehensively considers the geological factors including formation temperature, formation pressure, and the adsorption capacity of minerals, is innovative to a certain degree. As verified by the test data from the major exploration wells drilled in the Longfengshan area, the ranking criteria of tight reservoirs proposed in this study are effective and highly applicable and thus serve as effective guidance on the future exploration of the study area.